2020
DOI: 10.1039/d0ra06106a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of MOF-5 with mono-substituents: effects on drug delivery behavior

Abstract: Metal organic frameworks (MOFs) are widely used in drug carrier research due to their tunability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…In addition, after 48 and 72 h of treatment, the relative cell viability decreased in a gradual trend, which is a normal phenomenon. It should be noted that, on the basis of the literature, both MXene and MOF-5 are typically toxic nanomaterials; therefore, the obtained results of the cell viability are of great importance and a record by itself. The results of the dose-dependent MTT assay are detailed in the Supporting Information (Figures S1–S12).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, after 48 and 72 h of treatment, the relative cell viability decreased in a gradual trend, which is a normal phenomenon. It should be noted that, on the basis of the literature, both MXene and MOF-5 are typically toxic nanomaterials; therefore, the obtained results of the cell viability are of great importance and a record by itself. The results of the dose-dependent MTT assay are detailed in the Supporting Information (Figures S1–S12).…”
Section: Resultsmentioning
confidence: 99%
“…We used the solvent adsorption method to load curcumin onto IRMOF‐8, achieving a drug loading capacity of 57.85 ± 0.98 wt%. There are many potential mechanisms of interaction between curcumin and IRMOF‐8, including surface adsorption, pore encapsulation, and interaction between the host and guest [27]. In the release study, we found that the release rate of CUR@IRMOF‐8 was slow, but that it could be released continuously over a relatively long period time.…”
Section: Discussionmentioning
confidence: 96%
“…Metal-organic frameworks (MOFs) 1,2 have gained immense scientific interest for the construction of novel geometrical architectures in stable crystalline functional materials, which are applicable in fields including gas storage and separation, [3][4][5] catalysis, [6][7][8][9] ion exchange, 10,11 magnetism, [12][13][14][15] and drug delivery. [16][17][18][19] Among various applications, luminescence sensing based on luminescent MOFs has attracted significant attention due to their high selectivity, quick response, operability, and reversibility. 1,[20][21][22] A synthesized MOF can simultaneously detect multiple types of organic small molecules (such as explosives, antibiotics, amino acids, etc.…”
Section: Introductionmentioning
confidence: 99%